"Ecosystem Approach" versus "Sustainable Forest Management": Attempt at a comparison - Herrmann Ellenberg (Federal Research Centre for Forestry and Forest Products (BFH), Institute for World Forestry, 2003)
The follow-up negotiations to the Convention on Biological Diversity formulated the Ecosystem Approach, inter alia. The principles of this holistic approach are also important for the forestry sector and its management of forest ecosystems. In the light of the national debate and international forest policy negotiations, there is a need for German and European forestry to switch to the perspective of the Ecosystem Approach. This should be based on the regulatory framework on sound and sustainable forestry in Germany prescribed by forest legislation that has been further developed by technical regulations. This is all the more true as the issue 'Relationship between Ecosystem Approach and Sustainable Forest Management' had been incorporated into the ' Expanded Programme of Work Biological Diversity in Forests', adopted at the 6th Conference of the Parties to the Convention on Biological Diversity, to clarify its content. – – Im Rahmen der Folgeverhandlungen der Konvention über die Biologische Vielfalt wurde u. a. der Ecosystem Approach erarbeitet. Die Prinzipien dieses holistischen Ansatzes sind auch für die Forstwirtschaft und ihr Handeln im Ökosystem Wald von Bedeutung. Im Lichte der nationalen Diskussion und internationaler forstpolitischer Verhandlungen besteht die Notwendigkeit der Orientierung zur Sichtweise des Ecosystem Approach seitens der deutschen und europäischen Forstwirtschaft, ausgehend von dem forstrechtlich vorgegebenen und durch technische Vorschriften weiter ausgestalteten Regelwerk zur ordnungsgemäßen und nachhaltigen Forstwirtschaft in Deutschland. Dies gilt umso mehr, als die Fragestellung 'Verhältnis von Ecosystem Approach zu Sustainable Forest Management' in das 'Erweiterte Arbeitsprogramm über die biologische Vielfalt in Wäldern', das auf der 6. Vertragsstaatenkonferenz der Konvention über die Biologische Vielfalt beschlossen wurde, zur inhaltlichen Klärung aufgenommen wurde.
urn:nbn:de:gbv:253-200912-dk040076-8
Keywords: 630